Cross Accountability: A Model of Church Financial Accountability in A Synodal Presbyterial Perspective - Oktavianus Pasoloran; Hans Lura (Yayasan Riset dan Pengembangan Intelektual, 2023)
This study aims to build a model of church financial accountability in a synodal presbyterial perspective. The locus of this research is in the Toraja Church which is experiencing very rapid growth. The Church as the People of God is a pageantry that is in complete communion and still goes together, travels, thinks together, and acts together by imitating the teachings of Jesus Christ. By the Toraja Church, the teachings of Jesus were implemented in attachment to the Toraja Church Confession and the Toraja Church Order as a result of the trial of the Presbyters as Ecclesiastical Office Holders. Presbyters are instituted in Church assemblies with three ecclesiastical ministry offices: elder, deacon and pastor. The highest power is in the presbyter sessions, both in the scope of congregations, classics, regional synods and General synods. The results of this study show that accountability and accountability of the Toraja Church's finances and property in the spirit of presbyterial synodal is directed at cross accountability, namely horizontal accountability and vertical accountability. Horizontal accountability shows that (1) the property of the Toraja Church is used, supervised and examined within the framework of stewardship (stewarship), (2) the property of the Toraja Church is accountable to all stakeholders which is manifested in the accountability of the Church Assembly at each scope of the trial. While vertical accountability shows that (1) the property of the Toraja Church belongs to God who must be accounted for its management, (2) the property of the Toraja Church is used for God's glory in service. Therefore, accountability must be prepared by church assemblies who are given the responsibility of carrying out ministry activities within the scope of their organization. On the spiritual aspect, accountability by church assemblies means transcendence to God as the owner of all life and the universe.